Reformasi Praktik Notaris dengan Menjaga Tanggung Jawab Etika dan Integritas Profesional dalam Sistem Hukum Modern - Lovisna Devianti Widyatantri; Sukirno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The notary profession plays a crucial role in the legal system, particularly inensuring legal certainty and protecting the public interest. In recent years,technological developments and legal reforms have brought new challenges thatrequire a deeper understanding of a notary's ethical responsibilities. This study,using qualitative research, examines the importance of ethics in the notaryprofession, the challenges faced, and opportunities to improve professionalintegrity. The research method used was qualitative, with a literature review andanalysis of the applicable legal framework. The results indicate that a strongethical foundation is essential for notaries to maintain trust and credibility intheir work.